In Vitro Regeneration of High Yielding Indica Rice (Oryza sativa L.) Varieties - Alam, MJ; Imran, M; Hassan, L; Rubel, MH; Shamsuddoha, M (Journal of Environmental Science and Natural Resources, 2012)
The experiment was conducted to observe the regeneration potential and also to establish a suitable in vitro plantlet regeneration protocol from mature seed derived embryogenic calli of four indica rice varieties viz BRRI dhan28, BRRI dhan29, BRRI dhan47 and Binadhan-7 after partial desiccation treatment. Different concentrations and combinations of growth regulators were used in MS medium to observe the callus induction ability using mature embryo as explants. The percentage of callus induction frequency was highest (86.00) in BRRI dhan47 and the lowest (56.50) in Binadhan-7 Among the culture media the performance of MS +500 mgl-1 L- Proline + 2.0 mgl-12, 4-D + 0.8 mgl-1BAP was better than any other media for callus induction frequency (%), rapid callusing, size of the callus (mm), texture of callus and color of callus. Among the four varieties, shoot regeneration was highest in BRRI dhan29 (84.33%) which required minimum (14.80) days to and the lowest was in Binadhan-7 (39.67%) which required maximum (15.47) days. Among the treatments, the highest (65.75%) shoot regeneration was observed with MS + 6.0 mgl-1Kn +0.5 mgl-1 NAA which required minimum days (13.75) to develop green bud formation and the lowest shoot regeneration (56.50) was observed with MS + 2.0 mgl-1Kn + .05 mgl-1 NAA. BRRI dhan29 produced more number of shoots (4.67) per callus while Binadhan-7 showed minimum number of shoots (2.87) per callus. The highest number of shoot producing roots (3.66) was observed in BRRI dhan29 which showed maximum number of root per plant and the lowest (3.11) in Binadhan-7. Among the three treatments MS + 0.6 mgl-1IBA showed highest percentage 86.67 of root followed by MS+ 0.6 mgl-1IBA 70% and the lowest (66.7%) was in MS+ 0.4 mgl-1IBA. The establishment rate of the plantlet in the pot was the highest (67.67%) in BRRI dhan29 and Binadhan-7 showed lowest establishment rate (51.22%) in pot. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11573 J. Environ. Sci. & Natural Resources, 5(1): 173 - 177, 2012